MANAJEMEN KEARSIPAN PADA UPT BADAN PERPUSTAKAAN UMUM, ARSIP DAN DOKUMENTASI KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - ", Safriadi; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Document or archives management is one of the most important factors thatmust be considered in supporting the smoothness of all work processes that take place.Every institution always mingle with archives. As a public service provider, especiallyin archive processing services, whether it is borrowing or returning books, documents,correspondence, the UPT Public Library, Archives and Documentation of Sub-districtSiak Kecil should provide the best service to visitors and guided by the provisionswhich has been set. Informants in this research are Head of UPT, Head of Archives andDocumentation of Bengkalis Library, Staff and from public. Data analysis was donedescriptively qualitative. The result of the research stated that archive management atUPT Public Library, Archives and Documentation of Sub-district Siak Kecil has not runwell due to the work plan in archiving management that has not been done as it shouldbe and the obstacles that caused the unfulfilled archiving management plan. Factorsaffecting the archiving management in Public Library, Archives and Documentation ofSub-district Siak Kecil are limited personnel and facilities and infrastructure so that thecompletion of task will also be hampered. Organizing in archive management has notgone well because the archiving of both books and documentation has not gone wellbecause there are still shortcomings that must be fixed soon. Constraints in thepreparation of personnel in the UPT is in addition to the limited number of employees,skills and expertise. Briefing done by Head of UPT meeting of work plan evaluation.Keyword : Management, Archieves